Marinobacter mangrovi sp. nov., isolated from mangrove sediment. Issue 11 (11th November 2021) - Yi, En; Shao, Zongze; Li, Guizhen; Liang, Xiaobo; Zhou, Meixian
Abstract : A novel marine bacterium, designated strain CHFG3-1-5 T, was isolated from mangrove sediment sampled at Jiulong River estuary, Fujian, PR China. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain CHFG3-1-5 T belonged to the genus Marinobacter, with the highest sequence similarity to Marinobacter segnicrescens SS011B1-4 T (97.6%), followed by Marinobacter nanhaiticus D15-8W T (97.5%), Marinobacter bohaiensis T17 T (97.1%) and Marinobacter hydrocarbonoclasticus SP.17 T (90.6%). The bacterium was Gram-stain-negative, facultative anaerobic, oxidase- and catalase-positive, rod-shaped and motile with a polar flagellum. Strain CHFG3-1-5 T grew optimally at 32–37 °C, pH 6.0–8.0 and in the presence of 2.0–3.0% (w/v) NaCl. The G+C content of the chromosomal DNA was 61.1 mol%. The major respiratory quinone was determined to be Q-9. The principal fatty acids were C16 : 0, summed feature 3 (C16 : 1 ω 7 c / ω 6 c ), C12 : 0, summed feature 9 (C17 : 1 iso ω 9 c and/or C16 : 0 10-methyl), C12 : 0 3-OH and summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ). The polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, three phospholipids, one glycolipid and two aminolipids. The average nucleotide identity and digital DNA–DNA hybridization values among the genomes of strain CHFG3-1-5 T and the reference strains were 73.4–79.4 and 19.6–22.4%, respectively. Like many other species reported in the genus Marinobacter, strain CHFG3-1-5 T was able to oxidise iron. The combined genotypic and phenotypic data showed that strain CHFG3-1-5 T represents a novel species within the genus Marinobacter, for which the name Marinobacter mangrovi sp. nov. is proposed, with the type strain CHFG3-1-5 T (=MCCC 1A18306 T =KCTC 82398 T ).